Knowledge of Pulmonary Tuberculosis among the Patients under Anti- Tubercular Therapy (Bangladesh Journal of Infectious Diseases, 2018)
Background: Knowledge on tuberculosis is very important among the patients under anti-tubercular therapy for proper management.Objective: The purpose of the present study was to assess the knowledge about tuberculosis among patients attending the DOTS (directly observed treatment, short course) corner.Methodology: This cross sectional study was conducted in the DOTs corner of Sylhet MAG Osmani Medical College, Sylhet, Bangladesh and Sylhet Chest Disease Hospital, Sylhet, Bangladesh during the period from June 2011 to November 2011 for a period of six (6) months. All the patients who were diagnosed as case of pulmonary tuberculosis and were treated with anti-tubercular drugs at DOTs corner who attended in the both Hospitals, Sylhet were selected as study population.Result: The age of the patients ranged from 18 to 70 years with the mean age of 41.2 (SD+ 12.4) years. The age of the male patients were ranging from 18 to 70 years with the mean age of 42.1 (SD: 12.8) years. Among the 194 patients, 90(46.4%) patients had good knowledge and 104(53.6%) patients had poor knowledge about tuberculosis.Conclusion: In conclusion, greater efforts therefore need to be undertaken to improve TB control among TB patients through appropriate and sustainable health education.Bangladesh Journal of Infectious Diseases 2018;5(1):27-31